Experimental Facility at A2 Collaboration (MAINZ) for Photoproduction reaction (Journal of Nepal Physical Society, 2016)
Since 20 years, a very successful experimental program with real photons has been achieved at the Mainz Microtron (MAMI) facility. The A2 Collaboration at MAINZ is a unique place for the experimental facility of photoproduction reaction. The combination of highly sensitive photo spectrometers Crystal Ball and TAPS as forward wall detector along with particle identification detector and Multiwire proportional chambers as inner wall detectors provide the high precision of the measurement. MAMI-C, which consists of there Race Track Microtrons (RTMs) with the Harmonic Double -Sided Microtron (HDSM) is an intense, stable and continuous-wave accelerator to accelerate electron to 1.5 GeV. This electron beam is responsible to produce real photons via bremsstrahlung process at Glasgow Photon Tagger. A major part of the ongoing and future programme at MAMI will exploit polarised nucleon targets.Journal of Nepal Physical Society Vol.3(1) 2015: 73-81